Generation of Adducts of 4-Hydroxy-2-nonenal with Heat Shock 60 kDa Protein 1 in Human Promyelocytic HL-60 and Monocytic THP-1 Cell Lines - Arcaro, Alessia (Oxid Med Cell Longev, 2015)
Heat shock 60 kDa protein 1 (HSP60) is a chaperone and stress response protein responsible for protein folding and delivery of endogenous peptides to antigen-presenting cells and also a target of autoimmunity implicated in the pathogenesis of atherosclerosis. By two-dimensional electrophoresis and mass spectrometry, we found that exposure of human promyelocytic HL-60 cells to a nontoxic concentration (10 μM) of 4-hydroxy-2-nonenal (HNE) yielded a HSP60 modified with HNE. We also detected adducts of HNE with putative uncharacterized protein CXorf49, the product of an open reading frame identified in various cell and tissue proteomes. Moreover, exposure of human monocytic THP-1 cells differentiated with phorbol 12-myristate 13-acetate to 10 μM HNE, and to light density lipoprotein modified with HNE (HNE-LDL) or by copper-catalyzed oxidation (oxLDL), but not to native LDL, stimulated the formation of HNE adducts with HSP60, as detected by immunoprecipitation and western blot, well over basal levels. The identification of HNE-HSP60 adducts outlines a framework of mutually reinforcing interactions between endothelial cell stressors, like oxLDL and HSP60, whose possible outcomes, such as the amplification of endothelial dysfunction, the spreading of lipoxidative damage to other proteins, such as CXorf49, the activation of antigen-presenting cells, and the breaking of tolerance to HSP60 are discussed.